Augmented individual placement and support for people with serious mental illness: the results of a pilot study in Belgium - Knapen, Jan; MSc, Annick Myszta; Moriën, Yves (International Journal of Psychosocial Rehabilitation, 2018)
People with severe mental illness, especially those with a poor job history and somatic comorbidity, experience different psychosocial and physical barriers to employment. The aim of the present study was to examine the effectiveness of an augmented Individual Placement and Support (IPS) program, which consists of IPS and mental and psychomotor training among people with severe mental illness. During the period from May 2010 until December 2017, 176 clients participated in the study. Over 10 week period, people with severe mental illness receive IPS augmented with three group sessions per week of mental and psychomotor training (the I Care program). This program was based on a bio- psycho-social perspective, containing a combination of work-related psychological, educational and physical rehabilitation methods. The group consisted of people with mood, anxiety and adjustment disorders, autism spectrum syndrome, personality and psychotic disorders. Ninety (51.14%) participants had chronic medical diseases as well, mainly musculoskeletal diseases and/or chronic pain. The program resulted in a total employment 53.41% at 12 months. After three months competitive employment 97.85% of the clients was still at work. The results were compared with those reported in a Cochrane review.The integration of mental and psychomotor training in IPS (i.e. augmented IPS) would mitigate the psychosocial and physical barriers to employment such as, poorly controlled symptoms of mental and physical illness, low self-esteem and poor cognitive functioning and increases the employment rate.